A case of ulcerative colitis complicated with bronchiolitis obliterans organizing pneumonia (BOOP) and air leak syndrome - Müge AYDOĞDU,; Gül GÜRSEL,; Ezgi ÖZYILMAZ,; Nalan AKYÜREK,; Leyla MEMİŞ, (Turkish Journal of Gastroenterology, 2019)
-